Uncovering Food Waste Behavior and Its Determinants among Students at Universitas Ahmad Dahlan - Siti Mahsanah Budijati; Viki Arisandi Syem Edoardo; Ivani Kartika Cahyani Putri (The Indonesian Institute of Science and Technology Research, 2026)
Universitas Ahmad Dahlan (UAD) plans to advance the development of a green campus at Campus 4, with food waste management identified as a key supporting component. However, student behavior related to food waste has not yet been empirically examined, highlighting the need for this study. This research employed a multiple linear regression approach using questionnaire-based data collected from 421 students across 27 study programs at UAD Campus 4. The model tested the indirect influence of materialism, knowledge, and religiosity on food waste behavior, with environmental awareness functioning as a mediating variable. The findings indicate that UAD students’ food waste behavior has an average score of 3.14, suggesting that students tend to generate relatively low amounts of food waste. The model further reveals that materialism, knowledge, and religiosity exert indirect effects on food waste, and that environmental awareness significantly mediates the relationships between these predictors and food waste behavior. This study underscores the importance of enhancing students’ environmental awareness as an effective mechanism to reduce food waste and support the realization of a green campus.